Mycorrhizal fungi mitigate cadmium leaching losses by decreasing the inorganic cadmium proportion in soil solutions - Wei Li; Jiong Wu; Jie Yan; Xinran Liang; Xiaoyi Li; Yongmei He; Bo Li; Fangdong Zhan (Ecotoxicology and Environmental Safety)
Arbuscular mycorrhizal fungi (AMF) are common in cadmium (Cd)-contaminated soil. However, the effects of AMF on Cd migration in contaminated soil are still poorly understood. A pot experiment involving a control without AMF inoculation (CK), inoculation with AMF (AMF), and bacterial filtrate of the AMF inoculant (LY) was conducted in the present study. AMF caused an increase in total glomalin-related soil protein (T-GRSP) of 12.2 % and in the exudation of low-molecular-weight organic acids (LMWOAs), such as citric acid, malic acid, oxalic acid, and free amino acids, by maize roots of 30.4 %–200.0 % but caused a decrease in the Cd contents of the maize shoots and roots by 53.2 % and 47.2 %, respectively compared those of the CK. Moreover, AMF decreased the Cd concentration in the leachate by 36.0 %–76.3 % by reducing the proportion of Cd2 + and inorganic Cd complexes in the soil solution and leachate by 26.2 %–85.7 %, and increasing the proportion of organic Cd complexes. Structural equation analysis revealed that the GRSP and LMWOAs were the primary factors driving the potential of AMF to reduce Cd leaching loss from polluted soil. The adsorption of Cd ions by quartz sand increased with the application of GRSP and LMWOAs, which resulted in a 27.6 %–69.5 % reduction in Cd leaching loss in the sand column. In the soil with AMF, the proportion of organic-bound Cd increased and the proportion of inorganic-bound Cd decreased by promoting the secretion of LMWOAs via mycelium, thus reducing Cd leaching loss.